The Impact of Clinical Experience in Advanced Practice Nursing Education—A Cross-Sectional Study of Norwegian Advanced Practice Nurses’ Perspectives - Ann-Chatrin Linqvist Leonardsen (Nursing Reports, 2023)
Background: An Advanced Practice Nurse (APN) is a specialized nurse who has acquired context specific knowledge, complex decision-making skills, and clinical competencies. Previously in Norway, APN education programs had a prerequisite of a minimum of two years of clinical nursing experience. Recently, the government decided to abandon this prerequisite. Objectives: The objectives of this study were to assess APN’s and APN students’ (1) perspectives on the impact of clinical nursing experience on various aspects of nursing practice, (2) perspectives on the association between APN students’ previous clinical experience and the ability to achieve the learning outcomes in the education program, and (3) attitudes towards clinical nursing practice as a prerequisite before entry to APN education programs. Design: An observational, cross-sectional design. Methods: APN and APN students were invited to respond to a researcher-developed questionnaire. A snowballing sampling method was used. The questionnaire included 24 questions scored on a five-point Likert scale, and two questions with text responses. Quantitative data were analyzed using descriptive statistics, and text responses with thematic analysis. Results: In total, 1767 APNs (92.9%) and APN students (7.1%) responded. Between 93.6 and 98.2% of the respondents (n = 1767) agreed that clinical nursing experience leads to experience with communication, collaboration, basic procedures, medical equipment and documentation, and to the development of situation awareness, increased awareness on own role in teams, the ability to provide person-centered nursing, an independent nursing identity, and feeling of security. Over 90% of the respondents agreed that students’ previous clinical experience was associated with the ability to achieve the learning outcomes in the APN program. In addition, 93.7% of the respondents agreed that clinical nursing experience should be a prerequisite before entry to APN programs. Advantages of clinical experience were reported as ‘Professional identity’, ‘Intuitive grasp’, ‘Integration of technical skills’, and ‘See the whole picture’. Disadvantages were reported as ‘Prejudice and bad habits’, ‘The importance of relevant experience’, and ‘Recruitment issues’. Conclusion: This study adds insights into the impact of clinical nursing experience as a prerequisite to APN education programs. The results indicate that clinical nursing experience is an essential contributor to the development of nursing competence and a nursing identity. This study was not registered.